2019
DOI: 10.1128/aac.00865-19
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification, Antifungal Susceptibility Testing, and Mechanisms of Azole Resistance in Aspergillus Species Received within a Surveillance Program on Antifungal Resistance in Spain

Abstract: Antifungal resistance is one of the major causes of the increasing mortality rates for fungal infections, especially for those caused by Aspergillus spp. A surveillance program was established in 2014 in the Spanish National Center for Microbiology for tracking resistance in the most prevalent Aspergillus species. A total of 273 samples were included in the study and were initially classified as susceptible or resistant according to EUCAST breakpoints. Several Aspergillus cryptic species were found within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 50 publications
2
22
1
1
Order By: Relevance
“…We report the presence of TR 46 /Y121F/T289A now also from Iran, where until now only TR 34 /L98H had been isolated . This mutation, conferring voriconazole resistance, has been reported from both environmental (China, Taiwan, United Kingdom, Colombia, France, Germany, India, the Netherlands and Tanzania) and clinical sources (Spain, United Kingdom, France, Portugal, Argentina, Taiwan, Germany, China, Japan, United States, Denmark, Belgium and the Netherlands) (Table 1). All previous studies conducted in Iran for monitoring the mechanism of resistance among azole‐resistant A fumigatus in both clinical and environmental samples showed that the TR 34 /L98H mutation was reported with increasing frequency from 3.3% in 2013 to 6.6% in 2016 .…”
Section: Discussionmentioning
confidence: 73%
“…We report the presence of TR 46 /Y121F/T289A now also from Iran, where until now only TR 34 /L98H had been isolated . This mutation, conferring voriconazole resistance, has been reported from both environmental (China, Taiwan, United Kingdom, Colombia, France, Germany, India, the Netherlands and Tanzania) and clinical sources (Spain, United Kingdom, France, Portugal, Argentina, Taiwan, Germany, China, Japan, United States, Denmark, Belgium and the Netherlands) (Table 1). All previous studies conducted in Iran for monitoring the mechanism of resistance among azole‐resistant A fumigatus in both clinical and environmental samples showed that the TR 34 /L98H mutation was reported with increasing frequency from 3.3% in 2013 to 6.6% in 2016 .…”
Section: Discussionmentioning
confidence: 73%
“…Annual surveys in five academic hospitals in the Netherlands showed that azole resistance in A. fumigatus has doubled from 2014 to 2018 [23,24]. Similar data have been reported worldwide [25][26][27][28][29][30][31][32][33][34][35], and an international resistance surveillance group has been set up by ISHAM/ECMM to capture more information on azole resistance worldwide [36,37].…”
Section: Diagnosis Of Aspergillosismentioning
confidence: 76%
“…The TR46/Y121F/T289A is a less widespread but emerging azole resistance mutation, which was first reported in the Netherlands in 2009 [60]. Both resistance mechanisms are regularly recovered from environmental isolates worldwide [31,[61][62][63][64][65][66][67][68][69][70][71], and therefore are likely to have developed resistance from the substantial use of environmental azole fungicides [31,55,69,[72][73][74][75][76][77][78]. In 2017, the first azole-resistant A. fumigatus cyp51A TR46/Y121F/T289A mutant was isolated in the UK from a patient that had no prior history of azole antifungal use, suggesting resistance must have been acquired through the environment [79].…”
Section: Azole Resistancementioning
confidence: 99%
“…Several synonymous and non-synonymous point mutations were found among both susceptible and non-susceptible strains. One azole resistant strain (CM7668) harbored a c641t base change, resulting in a P214L point mutation that was only present in this strain, previously described in a recent work [ 36 ].…”
Section: Resultsmentioning
confidence: 98%
“… * A, azole drugs profile, S susceptible, R Resistant. 1 This mutation was previously described in a recent work [ 36 ]. …”
Section: Figurementioning
confidence: 99%